Kuwait : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2011)
Statistics of Kuwait's economics are presented in this paper. Some of the areas covered include gross domestic product prices, gross domestic expenditure; production, disposal, and prices of oil, and LPG consumer. Data on population and employment, summary of government finance, revenue, current expenditure, domestic subsidies and transfers are provided. The monetary survey balance sheet of local banks, interest rates with local banks, and net foreign assets of the financial sector as well as financial soundness indicators, external debt, and international investment position data are presented.